THE ROLE OF PUBLIC CONTROL IN THE DEVELOPMENT OF CIVIL SOCIETY - Khakimov, Orziqul; Rajabaliyev, Shavkat (Science technology&Digital finance, 2023)
Public control in the construction of civil society is a factor that serves to ensure that social justice is stable in society, with intolerance, equality, responsibility and responsibility in the relations of the individual, society and the state. It ensures that human rights and freedoms are not only guaranteed by the state, but also their priority in the activities of state bodies. Finally, the presence of public control is an indicator that political power, literally, is in the hands of the people. The authors expressed their opinion in this article that the activity of people in civil society, the lack of indifference to social phenomena, the need for each executive employee to teranly realize that his activities are under the control of the public are important in the development of society.